Quantity of IL-2, IL-4, IL-10, INF-γ, TNF-α and KC-Like cytokines in serum of Bitches with pyometra in different stages of oestrous cycle and Pregnancy - Maciel, G. S.; Uscategui, R. R.; de Almeida, V. T.; Oliveira, M. E.F.; Feliciano, M. A.R.; Vicente, W. R.R. (Wiley, 2014)
The occurrence of the pyometra is most common in the first half of the dioestrus when there is decreased cellular immunity associated with increased serum concentration of progesterone in females. The aim of this study was to determine the immunological profile of bitches with pyometra, studying serum levels of IL-2, IL-4, IL-10, IFN-γ, KC-like and TNF-α and comparing them with those of healthy bitches in anoestrus, dioestrus and pregnant. Forty females were divided into four experimental groups: group 1 (G1): with pyometra (n = 10); group 2 (G2): bitches in the second week of gestation (n = 10); group 3 (G3): in anoestrus (n = 10); and group 4 (G4): in dioestrus (n = 10). The serum levels for IL-2, KC-like, INF-γ and TNF-α were similar for all experimental groups. The values obtained for IL-10 were found increased (p < 0.001) in animals in dioestrus and pyometra compared with females in anoestrus and pregnant, and the levels of IL-4 observed were significantly greater (p < 0.001) in bitches with pyometra when compared with others. The cytokine profile in animals with pyometra is similar to bitches in dioestrus for IL-10 and had increase in IL-4 for bitches with pyometra, which represents an anti-inflammatory these cases. This suggests the presence of an immunosuppressive state in both cases, which may explain the propensity of bitches in dioestrus to be affected by pyometra and the severity of the disease on these animals. © 2014 Blackwell Verlag GmbH.